Maria nella lotta contro satana nel mondo d’oggi - Amato, SDB, Card. Angelo (Alpha Omega, 2017)
Summary: In the first part of the article, making use especially of the documents of the Church’s magisterium, the author analyses the presence and the activity of the devil in today’s world and the role of the Virgin Mary in the Church’s struggle against Satan. In the second part, he presents the event of Fatima as the interpretative counter-point to the work of Satanin destroying people’s minds and bodies, which has taken place in the 20th century and which continues in different ways in the present century. Making use here too of the documents of recent magisterium, above all Papal magisterium, he shows how the message of Fatima sheds a light upon humanity that is both realistic and yet full of great hope. Key words: Virgin Mary, Church, Satan, devil, satanic, today’s world, anti-Catholic persecution, Fatima, secret of Fatima, Sister Lucia, Immaculate Heart. Parole chiave: Vergine Maria, Chiesa, Satana, diavolo, satanico, mondo odierno, persecuzione anticattolica, Fatima, segreto di Fatima, Suor Lucia, Cuore Immacolato.